The preservation management handbook a 21st-century guide for libraries, archives, and museums - Conn, Donia 1968- (Rowman & Littlefield, 2020)
Museum curators, museum professionals, archivists and librarians from small local history museums to world-famous art and natural history collections, must deploy their specialized knowledge to prioritize the needs of their collections. This revised volume has a wide range of topic-specific expertise that comprises both an enduring text for preservation students as well as an essential one-stop reference for cultural heritage professionals where resources are limited and professional help is not always at hand"--